Utilization of garcinia mangostana dyes for superhydrophobic oncotton textile application - Marsi, Noraini; Sum, Man Kent; Mohd Rus, Anika Zafiah; Mohd Harun, Dalila (Penerbit UTHM, 2020)
The demand for textile products has increases rapidly nowadays and so did the production. Hence, people tend use synthetics dyes because it is cheaper and more durable as compared to natural dyes. Therefore, synthetic dyes has contributed to dye wastewater and becomes one of the causes of outrageous pollution in nowadays. Factories that discharge this wastewater as harmful toxic waste, colourfull and organic chemicals from dyeing. Chemicals such as sulphur, vat dyes, arsenic, and certain auxiliary chemicals make the wastewater highly toxic and poisonous [1]. In order to overcome this problem, an alternative way has to be found. One of the alternative way is to make a good use of the waste from the nature, for example, the peel of mangosteen. Mangosteen or known as Garcinia mangostana is one of the fruits that can be found easily in Malaysia during monsoon season. So, the difficulty of getting these fruits are not very hard. However, the rind of mangosteens are non-edible and being thrown unknowingly by most of the people in Malaysia. The rinds of the fruits contain high level of anthocyanin pigments which can be used in dyeing application of fabric. The utilization of fruit hulls of Garcinia mangostana will help to reduce biodegradable wastes in the environment. Its reuse or recycling will also aids in the halting of the release of greenhouse gases. Natural dyes are beneficial to the environment and it can reduces the water pollution [2].